Does vibration warm-up enhance kinetic and temporal sprint parameters? - Cochrane, D. J.; Cronin, M. J.; Fink, P. W. (International Journal of Sports Medicine, 2015)
The aim of this study was to investigate the efficacy of vibration warm-up to enhance sprint performance. 12 males involved in representative team sports performed 4 warm-up conditions in a randomised order performed at least 24h apart; VbX warm-up (VbX-WU); Neural activation warm-up (Neu-WU); Dynamic warm-up (Dyn-WU) and Control (No VbX). Participants completed 5m sprint at 30s, 2:30min and 5min post warm-up where sprint time, kinetics, and temporal components were recorded. There was no significant (p>0.05) main effect or interaction effect between the split sprint times of 1m, 2.5 m, and 5 m. There was a condition effect where vertical mean force was significantly higher (p<0.05) in Dyn-WU and Control compared to Neu-WU. No other significant (p>0.05) main and interaction effects in sprint kinetic and temporal parameters existed. Overall, all 4 warm-up conditions produced comparable results for sprint performance, and there was no detrimental effect on short-duration sprint performance using VbX-WU. Therefore, VbX could be useful for adding variety to the training warm-up or be included into the main warm-up routine as a supplementary modality.